2021
DOI: 10.1016/j.ijid.2021.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a 5-minute infusion versus the standard 30-minute infusion for antibiotics in an outpatient setting

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Over a median treatment duration of 21 days and a combined 4326 doses given to 184 patients, the study found no rapid infusion-related adverse reactions and concluded that IVP for OPAT is clinically safe and well tolerated. 39 Another retrospective cohort study conducted within a health system evaluated the incidence of adverse events with IVP beta-lactams during the aforementioned 2017 national shortage of smallvolume parenteral solutions. In adult patients who received a 5-min slow IVP of aztreonam, ceftriaxone, cefepime, or meropenem, a total of 10 adverse events were identified among 1000 patients (1%).…”
Section: Safety Of Ivp Antimicrobialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over a median treatment duration of 21 days and a combined 4326 doses given to 184 patients, the study found no rapid infusion-related adverse reactions and concluded that IVP for OPAT is clinically safe and well tolerated. 39 Another retrospective cohort study conducted within a health system evaluated the incidence of adverse events with IVP beta-lactams during the aforementioned 2017 national shortage of smallvolume parenteral solutions. In adult patients who received a 5-min slow IVP of aztreonam, ceftriaxone, cefepime, or meropenem, a total of 10 adverse events were identified among 1000 patients (1%).…”
Section: Safety Of Ivp Antimicrobialsmentioning
confidence: 99%
“…Over a median treatment duration of 21 days and a combined 4326 doses given to 184 patients, the study found no rapid infusion-related adverse reactions and concluded that IVP for OPAT is clinically safe and well tolerated. 39 …”
Section: Clinical Datamentioning
confidence: 99%
“…4,5 Antibiotics are vital drugs that are effective against and prevent bacterial infection. 6,7 To date, hundreds of antibiotics have been commercialized and applied in human disease treatment, aquaculture and husbandry. [8][9][10] Antibiotics are excessively abused in and discharged from livestock and poultry, and superuous residuals overow from aquaculture production.…”
Section: Introductionmentioning
confidence: 99%